KERJASAMA INDONESIA-JEPANG DALAM EKSPOR BATUBARA TAHUN 2014-2017 - M.Fidel Katsro; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study describe Indonesia's economic cooperation in coal exports to Japan in 2014-2017, which was written in the Joint Statement of the Indonesia Japan Economic Partnership Agreement (IJEPA) on August 20, 2007. The sources of this research were obtained through literature reviews, books, websites, and others. The source of analysis is qualitative methods. This study uses the level of analysis of the nation state, liberalism perspective considers that war is only a small part of existing reality. The liberalists hope international relation are understood throughly and not forget thatcooperation between countries is one of themain things. Indonesia is one of the biggest coal producing countries, and Japan is an industrial country that needs energy to run its industry. This economic cooperation is a Japanese soft power strategy that has helped the Indonesian economy. Seeing the condition of Japan that really needs energy, one of which is coal. Indonesian coal exports are very instrumental in increasing the country's foreign exchange, with the existence of economic cooperation, especially in the energy sector, Japan as a partner also helps in the development of Indonesian coal.Keywords: Coal, Energy, Export, Import, Economic Cooperation, IJEPA.